GERAKAN BERSAMA: MENJAGA KEBERSIHAN LINGKUNGAN DAN MENGURANGI SAMPAH DI PANTAI TAMENDAO GORONTALO - Liayong Pratama, M Iqbal; Yusuf, Daud; Maryati, Sri; Rusiyah, Rusiyah; Kobi, Wiwin; Masruroh, Masruroh; Pambudi, Moch Rio; Asrul, Asrul (Sekolah Tinggi Agama Katolik Negeri Pontianak, 2024)
In the context of increasing global concern for environmental issues, beach cleaning activities at Tamendao Beach in Gorontalo have become very important as a response to the accumulation of plastic waste, which threatens the coastal environment and marine biota. This activity aims to increase public awareness of the importance of maintaining environmental cleanliness, especially in coastal areas, and reduce plastic waste accumulation through cross-sector collaboration and active community participation. The methods used include initial surveys to evaluate the level of rubbish accumulation, planning cleanup strategies, resource mobilization, participant training, and beach cleanup activities involving sorting and processing rubbish. The results show success in collecting large amounts of plastic waste, increasing public environmental awareness, and showing the importance of cross-sector collaboration in maintaining a clean environment. In conclusion, this activity had a significant positive impact on the surrounding environment. It emphasized the need for a follow-up plan to ensure the sustainability of environmental conservation efforts at Tamendao Beach and the surrounding area.